EVALUASI PENERAPAN SISTEM PENGENDALIAN MUTU KANTOR AKUNTAN PUBLIK BERDASARKAN SPAP IAPI TAHUN 2013 - Maulina Rahmawati (COMPETITIVE, 2022)
This study aims to examine the suitability of the implementation of the quality control system in the Public Accounting Firm "X" with the quality control system of the public accounting firm which is regulated in the Public Accounting Standards called SPAP, especially those regulated in the Quality Control Standards (SPM) No.1 of 2013 and SA (220). The method used is through the method of literature study, interviews, and questionnaires. The results of the review that have been carried out show that in general the Public Accounting Firm "X" has not established a quality control system that is in accordance with the overall SPM.